2008
DOI: 10.1063/1.2947587
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature terahertz detection based on bulk plasmons in antenna-coupled GaAs field effect transistors

Abstract: Cooperative absorption of terahertz radiation by plasmon modes in an array of field-effect transistors with twodimensional electron channel Simple technique to determine the drain temperature in GaAs metal semiconductor field effect transistor J. Appl. Phys. 93, 6344 (2003); 10.1063/1.1566475 Temperature dependence of noise in a GaAs metal-semiconductor field effect transistor at microwave frequencies Appl.Dry etch damage in GaAs metal-semiconductor field-effect transistors exposed to inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
(5 reference statements)
0
20
0
Order By: Relevance
“…It is found that the quantum ring intersublevel detectors (QRIDs) exhibit very low dark current and strong response in the 1-3 THz range, with the peak response measured at 1.82 THz (165 μm) in the temperature range of 5-10 K. This detection peak is characterized by a peak responsivity of 25 A/W and specific detectivity of 1×10 16 Jones [298]. THz detector response can be enhanced by surface plasmon effects [299][300][301]. When the energy of the plasma− −wave frequencies is quantized, the quanta are called plas− mons.…”
Section: Novel Thz Detectorsmentioning
confidence: 98%
“…It is found that the quantum ring intersublevel detectors (QRIDs) exhibit very low dark current and strong response in the 1-3 THz range, with the peak response measured at 1.82 THz (165 μm) in the temperature range of 5-10 K. This detection peak is characterized by a peak responsivity of 25 A/W and specific detectivity of 1×10 16 Jones [298]. THz detector response can be enhanced by surface plasmon effects [299][300][301]. When the energy of the plasma− −wave frequencies is quantized, the quanta are called plas− mons.…”
Section: Novel Thz Detectorsmentioning
confidence: 98%
“…4 It is naturally expected that a resonant response would allow for more sensitive detection and also allow for spectral resolution. [4][5][6][7][8][9][10][11][12] However, experimental results reported so far show that the resonant response is much weaker than the nonresonant response and the former is usually submerged into the latter. [5][6][7] The amplitude of the resonant response is limited by the quality factor (Q ¼ x p s p , where x p is the plasmon's angular frequency and s p is the plasmon's relaxation time) of the plasmon resonance.…”
mentioning
confidence: 87%
“…Plasmon-resonant detectors have recently received attention [9]. Also, plasmon-based field effect transistors operating at room temperature have been demonstrated [10,11]. In general, broadband detectors such as bolometers or Golay cells suffer from slow response time or cryogenic operation.…”
Section: Introductionmentioning
confidence: 99%